Outcome of Thyroid Surgeries at Patan Hospital - Yadav, Deepak; Dangol, Bhawana; GC, Anita; Shrestha, Namita; Devkota, Ishwor Raj; Nepal, Ajit (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Objective: To assess the outcome of thyroid surgeries at Patan HospitalMaterials and Methods: It is a retrospective study of in-patient records of patients undergoing thyroid surgeries for various indications from April 2013 to January 2015 at Patan Hospital, Lalitpur.Results: During the period of 21 months, 75 patients underwent thyroid surgeries. Majority of patients underwent hemithyroidectomy (35) followed by total thyroidectomy (28), subtotal thyroidectomy (7) and completion thyroidectomy (5). Out of 28 patients undergoing total thyroidectomy (TT), 11 underwent central compartment clearance (CCC), 5 underwent CCC and lateral neck dissection. Among 5 patients undergoing completion thyroidectomy, CCC was performed in all cases and in one patient lateral neck dissection was also performed.  A total of 13 patients developed unilateral recurrent laryngeal nerve palsy (RLN), among them 5 had permanent palsy. Tracheostomy had to be done in immediate postoperative period for stridor following total thyroidectomy (TT) in one case. Temporary hypocalcaemia was observed in 10 (10/28) cases following TT, out of which 8 had undergone CCC. Permanent hypocalcaemia was observed in 7 (7/28) cases following TT out of which 3 had undergone CCC. Chylous leak occurred in one of the patient undergoing left level II-IV neck dissection which was managed conservatively. None of the patient had to be transfused postoperatively.Conclusion: Complications to thyroid surgery are not uncommon. Visualization of recurrent laryngeal nerve alone in our context is adequate in experienced hands. Identification of parathyroid during thyroidectomy is recommended to avoid hypocalcaemia. Meticulous dissection can reduce the complications.Nepalese Journal of ENT Head and Neck Surgery, Vol. 6, No. 1, 2015